Adequacy of Infant Formula With Protein Content of 1.6 g/100 kcal for Infants Between 3 and 12 Months. Issue 5 (November 2015) - Ziegler, Ekhard E.; Fields, David A.; Chernausek, Steven D.; Steenhout, Philippe; Grathwohl, Dominik; Jeter, Janice M.; Nelson, Steven E.; Haschke, Ferdinand
ABSTRACT: Objectives: Infant formulas provide more protein than breast milk. High protein intakes may place infants at risk of later obesity. The present study tested whether a formula with protein content below the regulatory level supports normal growth from age 3 months. Methods: Randomized double-blind trial enrolled healthy infants less than age 3 months. At 3 months, formula-fed infants were assigned to experimental (EXPL, 1.61 g protein/100 kcal; modified bovine whey proteins with caseinoglycomacropeptide removed) or control (CTRL 2.15 g protein/100 kcal; unmodified bovine milk protein with a whey/casein ratio of 60/40) formula; breast-fed (BF) infants were enrolled in a reference group. Complementary foods were allowed in small amounts from 4 to 6 months and unrestricted after 6 months. Results: Weight gain (g/day) from 3 to 6 months was similar in the EXPL and CTRL groups (EXPL-CTRL −0.84 g/day; 95% confidence interval −2.25 to 0.57) and faster in the EXPL and CTRL groups than in the BF group. Weight analyzed longitudinally from 4 to 12 months was lower in the EXPL group than in the CTRL group ( P = 0.031) but higher than in the BF group ( P < 0.0001). Longitudinal analysis of odds ratios from 4 to 12 months indicated fewer infants with weight >85th percentile in the EXPL group than in the CTRL group ( P = 0.015). Length z scores were lower than, and body mass index z scores were similar to, World Health Organization Standards in all of the groups. Serum biochemical parameters in the EXPL group reflected lower protein intake and were closer to parameters in the BF infants than in the CTRL group. Conclusions: A formula with 1.61 g of protein/100 kcal supports normal growth of infants after age 3 months. This protein content is adequate if provided from a high-quality source. Abstract : Supplemental Digital Content is available in the text